AlepPBP2, but not AlepPBP3, may involve in the recognition of sex pheromones and maize volatiles in Athetis lepigone. Issue 4 (24th August 2022) - Yang, Hui-Hui; Xu, Ji-Wei; Zhang, Xiao-Qing; Huang, Jian-Rong; Li, Lu-Lu; Yao, Wei-Chen; Zhao, Pan-Pan; Zhang, Dong; Liu, Jia-Yi; Dewer, Youssef; Zhu, Xiu-Yun; Li, Xiao-Ming; et al.
Abstract: Athetis lepigone Möschler (Lepidoptera, Noctuidae) is a common maize pest in Europe and Asia. However, there is no long-term effective management strategy is available yet to suppress its population. Adults rely heavily on olfactory cues to locate their optimal host plants and oviposition sites. Pheromone-binding proteins (PBPs) are believed to be responsible for recognizing and transporting different odorant molecules to interact with receptor membrane proteins. In this study, the ligand-binding specificities of two AlepPBPs (AlepPBP2 and AlepPBP3) for sex pheromone components and host plant (maize) volatiles were measured by fluorescence ligand-binding assay. The results demonstrated that AlepPBP2 had a high affinity with two pheromones [(Z)-7-dodecenyl acetate, Ki = 1.11 ± 0.1 μ M, (Z)-9-tetradecenyl acetate, Ki = 1.32 ± 0.15 μ M] and ten plant volatiles, including (-)-limonene, α -pinene, myrcene, linalool, benzaldehyde, nonanal, 2-hexanone, 3-hexanone, 2-heptanone and 6-methyl-5-hepten-2-one. In contrast, we found that none of these chemicals could bind to AlepPBP3. Our results clearly show no significant differences in the functional characterization of the binding properties between AlepPBP2 and AlepPBP3 to sex pheromones and host plant volatiles. Furthermore, molecular docking was employed for further detail on some crucial amino acid residues involved in the ligand-binding of AlepPBP2. These findings will provide valuable information about the potential protein binding sites necessary for protein-ligand interactions which appear as attractive targets for the development of novel technologies and management strategies for insect pests.